Management of stable flies in cattle feedlots with releases of parasitic wasps - G.L. Greene; J.E. Cilek (Kansas Agricultural Experiment Station Research Reports, 1993)
During 1992, adult stable fly populations were sampled in 25 Kansas feedlots. A native stable fly parasitic wasp, Spalangia nigroaenea, was released in 19 of these feedlots. Stable fly populations were reduced up to 48% and parasite emergence was increased 21% when compared with feedlots where S. nigroaenea was not released. The percentage of total parasites that were S. nigroaenea nearly doubled in the release feedlots, compared to the nonrelease feedlots. This parasitic wasp has shown considerable promise for stable fly control in cattle feedlots. Overall, sampling and parasite costs averaged 32 cents per animal for the season.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Stable fly; Pteromalidae; Spalangia nigroaenea; Cattle feedlots; Fly management